Distinct Trauma Types in Military Service Members Seeking Treatment for Posttraumatic Stress Disorder. Issue 2 (18th April 2018) - Litz, Brett T.; Contractor, Ateka A.; Rhodes, Charla; Dondanville, Katherine A.; Jordan, Alexander H.; Resick, Patricia A.; Foa, Edna B.; Young‐McCaughan, Stacey; Mintz, Jim; Yarvis, Jeffrey S.; Peterson, Alan L.; ,
Abstract: We examined the frequency of trauma types reported in a cohort of service members seeking treatment for posttraumatic stress disorder (PTSD) and compared symptom profiles between types. In this observational study, 999 service members (9.2% women; M age = 32.91 years; 55.6% White) were evaluated using a standardized assessment procedure to determine eligibility for clinical trials. Participants were evaluated for DSM‐IV‐TR ‐defined PTSD using the PTSD Symptom Scale–Interview; all participants reported a Criterion A event. Independent evaluators rated descriptions of Criterion A events as belonging to trauma types at a high degree of reliability, κ = 0.80. Aggregated non‐life‐threat primary trauma types were more frequently endorsed than aggregated life‐threat types, 95% CI [17.10%, 29.20%]. Participants who endorsed moral injury–self traumas had a higher level of reexperiencing ( d = 0.39), guilt (hindsight bias, d = 1.06; wrongdoing, d = 0.93), and self‐blame ( d = 0.58) symptoms, relative to those who reported life threat–self. Participants who experienced traumatic loss had greater reexperiencing ( d = 0.39), avoidance ( d = 0.22), guilt (responsibility, d = 0.39), and greater peri‐ and posttraumatic sadness ( d = 0.84 and d = 0.70, respectively) symptoms, relative to those who endorsed life threat–self. Relative to life threat–self, moral injury–others was associated with greater peri‐ ( d = 0.36) and posttraumatic ( d = 0.33) betrayal/humiliation symptoms, and endorsement of aftermath of violence was associated with greater peri‐ ( d = 0.84) and posttraumatic sadness ( d = 0.57) symptoms. War zone traumas were heterogeneous, and non‐life‐threat traumas were associated with distinct symptoms and problems.